(untitled) (Journal of Bangladesh Academy of Sciences, 2012)
Seifert-Van Kampen theorem for the sum X + Y and external sum X ⊕Y of topological spaces is studied and the fundamental groups of these sums have been determined. Key words: Sum; External sum; Fundamental group; Commutative diagram DOI: http://dx.doi.org/10.3329/jbas.v35i2.9424 JBAS 2011; 35(2): 197-201